2021
DOI: 10.3390/microorganisms9051023
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Phenotypic Analysis of Linezolid-Resistant Staphylococcus epidermidis in a Tertiary Hospital in Innsbruck, Austria

Abstract: Whole genome sequencing is a useful tool to monitor the spread of resistance mechanisms in bacteria. In this retrospective study, we investigated genetic resistance mechanisms, sequence types (ST) and respective phenotypes of linezolid-resistant Staphylococcus epidermidis (LRSE, n = 129) recovered from a cohort of patients receiving or not receiving linezolid within a tertiary hospital in Innsbruck, Austria. Hereby, the point mutation G2603U in the 23S rRNA (n = 91) was the major resistance mechanism followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…The presence of the cfr gene, which encodes 23S rRNA methylases A2503, plays a crucial role in the development of PhLOPS A phenotype. Many published reports stated that cfr gene-carrying isolates showed higher phenotypic resistance levels compared to cfr -negative isolates [6, 22, 31, 32]. In the present study, all of the cfr -carrying isolates exhibited the PhLOPS A phenotype, including phenotypically susceptible isolates that carried cfr gene, which confers resistance to phenicols, lincosamides, oxazolidinones, pleuromutilins and streptogramin A antibiotics.…”
Section: Lrsh Isolatessupporting
confidence: 53%
See 1 more Smart Citation
“…The presence of the cfr gene, which encodes 23S rRNA methylases A2503, plays a crucial role in the development of PhLOPS A phenotype. Many published reports stated that cfr gene-carrying isolates showed higher phenotypic resistance levels compared to cfr -negative isolates [6, 22, 31, 32]. In the present study, all of the cfr -carrying isolates exhibited the PhLOPS A phenotype, including phenotypically susceptible isolates that carried cfr gene, which confers resistance to phenicols, lincosamides, oxazolidinones, pleuromutilins and streptogramin A antibiotics.…”
Section: Lrsh Isolatessupporting
confidence: 53%
“…Linezolid is not suitable for treating infections caused by Gram-negative organisms that are intrinsically resistant due to efflux pumps that export linezolid out of the cell quicker than it can accumulate. Both Zyvox Annual Appraisal of Potency and Spectrum (ZAAPS) and Linezolid Experience and Accurate Determination of Resistance (LEADER) surveillance programmes have found that Gram-positive organisms have a susceptibility rate of >99 % to linezolid [22]. However, case reports of acquired LR in clinical staphylococcal isolates with various resistance mechanisms were published immediately after the introduction of linezolid in clinical practice.…”
Section: Lrsh Isolatesmentioning
confidence: 99%
“…Altered target sites can be generated by random point mutations that accumulate during growth and can expand to dominance under drug pressure. Alternatively, mutant alleles of target genes can be generated at high frequency by recombination between alleles if multiple copies exist within the cell (for example, mutation and recombination between homologues of the 23S ribosomal RNA (rRNA) gene can rapidly confer linezolid resistance in Gram-positive species 78 ) or by transformation, whereby alternative alleles can be gained from related species and mosaic genes are generated by recombination, an approach common in competent species such as members of the Neisseria genus 79 .…”
Section: Target Alteration Modification and Protectionmentioning
confidence: 99%
“…Linezolid-resistant phenotype is most often associated with multidrug resistance, directly related to the mechanism involved, or to the combination with other resistance mechanisms ( 13 ). It may be subject to clonal epidemic dissemination as already described in several hospital departments, including French ones ( 14 19 ).…”
Section: Introductionmentioning
confidence: 82%